Therapeutic drug monitoring in inflammatory bowel disease - Kopylov, Uri (Hellenic Society of Gastroenterology, 2014)
Tumor necrosis factor (TNF)-α inhibitors and thiopurines are among the most important classes of medications utilized in the clinical management of Crohn’s disease and ulcerative colitis. A significant proportion of patients loses response to these agents or develops adverse effects during the course of the treatment. Monitoring of drug levels and anti-drug antibodies (for TNF-α inhibitors) and metabolite levels (for thiopurines) can provide valuable insight into the possible etiology of unfavorable outcomes and allow for an appropriate management strategy for these patients. This review summarizes the current knowledge on the clinical implications of therapeutic drug monitoring in inflammatory bowel disease patients treated with TNF-α inhibitors and thiopurines.